Judicial review of administrative action across the common law world : origins and adaptation / edited by Swati Jhaveri, Michael Ramsden. - Jhaveri, Swati; Ramsden, Michael (Cambridge University Press, 2021)
Research on comparative administrative law, in contrast to comparative constitutional law, remains largely underdeveloped. This book plugs that gap. It considers how a wide range of common law systems have received and adapted English common law to the needs of their own socio-political context. Readers will be given complex insights into a wide range of common law systems of administrative law, which they may not otherwise have access to given how difficult it would be to research all of the systems covered in the volume single-handedly. The book covers Scotland, Ireland, the USA, Canada, Israel, South Africa, Kenya, Malaysia, Singapore, Hong Kong SAR, India, Bangladesh, Australia and New Zealand. Comparative public lawyers will have a much greater range of common law models of administrative law - either to pursue conversations about their own common law system or to sophisticate their comparison of their system (civil law or otherwise) with common law systems.